2010
DOI: 10.1128/iai.00783-10
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Protein X (Ail) Contributes to Yersinia pestis Virulence in Pneumonic Plague and Its Activity Is Dependent on the Lipopolysaccharide Core Length

Abstract: Yersinia pestis, the causative agent of plague, is one of the most virulent microorganisms known. The outer membrane protein X (OmpX) in Y. pestis KIM is required for efficient bacterial adherence to and internalization by cultured HEp-2 cells and confers resistance to human serum. Here, we tested the contribution of OmpX to disease progression in the fully virulent Y. pestis CO92 strain by engineering a deletion mutant and comparing its ability in mediating pneumonic plague to that of the wild type in two ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(124 citation statements)
references
References 60 publications
(83 reference statements)
5
118
0
1
Order By: Relevance
“…RNA-sequencing, quantitative proteomics and RT-qPCR revealed unanimously a reduction in the level of Ail in the mutant strain, which could explain the observed impairment in adhesion. This is in accordance with previous findings showing an ail mutant leads to a severe reduction in adhesion (Felek & Krukonis, 2009;Kolodziejek et al, 2010). In spite of the decrease in adhesion, the ybeY bacteria that had adhered were still able to enter the cells at the WT level, suggesting that the process of invasion itself was not affected.…”
Section: Discussionsupporting
confidence: 81%
“…RNA-sequencing, quantitative proteomics and RT-qPCR revealed unanimously a reduction in the level of Ail in the mutant strain, which could explain the observed impairment in adhesion. This is in accordance with previous findings showing an ail mutant leads to a severe reduction in adhesion (Felek & Krukonis, 2009;Kolodziejek et al, 2010). In spite of the decrease in adhesion, the ybeY bacteria that had adhered were still able to enter the cells at the WT level, suggesting that the process of invasion itself was not affected.…”
Section: Discussionsupporting
confidence: 81%
“…For example, a drastic decrease of the concentration of OmpF has been observed in E. coli LPS mutants (45). Ail-mediated resistance to human serum depends on the LPS core (39), and changes in the LPS structure may influence the Ail conformation and specific activity (38). However, whether the receptor functions of Ail and OmpF are related to the LPS core remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…OmpF is often regarded as a classical porin, which is present in large quan- tities, and is also required as a receptor by several phages of E. coli (31,36,37). Ail protein is essential for Y. pestis to resist complement-mediated killing, and Ail-mediated resistance to human serum depends on the LPS core (38,39). However, the function of Ail in phage receptors has yet to be fully explained.…”
Section: Resultsmentioning
confidence: 99%
“…This capsule enhances resistance to engulfment by both macrophages and neutrophils, probably by preventing interactions of receptors that could facilitate uptake of the pathogen (Du et al, 2002). It was also observed that Y. pestis produces a less-acylated (tetra-acylated) lipid A at 37 °C, which results in poor induction of host tolllike receptor (TLR) 4-mediated innate immune responses and ultimately poor activation of human macrophages (Kawahara et al, 2002;Kolodziejek et al, 2010). When Y. pestis KIM1001, which expresses a poorly TLR4-stimulating LPS, was modified to strongly induce TLR4, it became avirulent (Montminy et al, 2006).…”
Section: Immunology Of Y Pestismentioning
confidence: 96%
“…Genes for additonal virulence proteins such as, Ail (attachment invasion locus, also designated as OmpX), plasminogen activator protease (Pla), and pH 6 antigen (Psa) have been deleted in an effort to generate effective live attenuated vaccine strains (Felek et al, 2010). In a pneumonic plague model, animals infected with a ompX mutant of Y. pestis CO92 survived for two days longer than those infected with the parent strain (Kolodziejek et al, 2010). Moreover, Δcaf1 mutants and ΔpsaA mutants exhibited decreased virulence in a murine infection model (Weening et al, 2011).…”
Section: Wwwintechopencommentioning
confidence: 99%